Fast switching of the rf trapping field in an ion trap - Laura Blackburn; Amber Shepherd; Matthias Keller (New Journal of Physics)
Radiofrequency ion traps are essential for many experiments, ranging from quantum computing to physical chemistry and fundamental science. However, in some circumstances the trapping fields may cause undesired effects and need to be switched off briefly during operation without compromising the trap stability. By employing interference in the trap resonator circuit to enable switching faster than the resonator’s natural decay, the electric field in the trap can be extinguished by $\gt$ 50 dB. We have demonstrated that it is possible to switch a linear Paul trap off for several microseconds without the loss of ^40 Ca ^+ ions, even for large three-dimensional ion crystals, and have examined the effect of the switching parameters on the ion dynamics by monitoring the fluorescence rate. We have loaded N ${\,}_2^+$ ions into a crystal of trapped calcium ions via photoionisation using this technique, demonstrating that it is also possible to capture ions despite the absence of a trapping field during the ionisation.